Number of Node Estimation in Mobile Ad Hoc Networks - Manaseer, Saher; Alhabash, Ibrahem (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Mobile Ad hoc networks do not have any form of centralized control as per their definition. Therefore, many challenges face the development of efficient protocols for such networks. One of the main challenges is the difficulty of extracting the total number of nodes in the network, this paper aims to find an estimate for this number using the average hop count for messages exchanged in the network. Experiments of this paper are conducted on Ad Hoc networks under DSR and AODV routing protocols. Results show a relation between network size and average hop count that can be used to predict the number of nodes in the network.